PENGARUH STRATEGI POSITIONING TERHADAP KEPUTUSAN PEMBELIAN PRODUK JASA ASURANSI PADAPT. JIWASRAYA DI TANGERANG - Abdul Karim Butar-butar (JMB : Jurnal Manajemen dan Bisnis, 2018)
The purpose of this research is to identify and analize the effect ofpositioning strategy to product, price and service on the decision purchasecostumer at PT. Jiwasraya in Tangerang. Population is customer of PT.Jiwasraya in Tangerang. The sampling technique used purposive samplingmethod that is sampled because someone happened to be in thisresearch at PT. Jiwasraya in Tangerang. This research used multiple linierregression analysis with sigifikan alpha 5%. The result showed thatproduct, price and service have significant effect to the decision purchasecustomer at PT. Jiwasraya in Tangerang. The partial test showed thatproduct and price have positive and significant to the decision purchasecostumer at PT. Jiwasraya in Tangerang. Service have positive and notsignificant to the decision purchase costumer at PT. Jiwasraya inTangerang. Through testing the adjusted coefficient of determination(Adjusted R square) obtained a value of 0,611 or 61,1% the decisionpurchase customer decision as the dependent variable can be explainedby the product, price, and service as independent variables. While theremaining 38,9% can be explained by other variables not examined inthis study.